203k views
5 votes
Simplify the expression

3x^2y^-1/2x • 10x^2y/3y^-3

*these two are fractions being multiplied if you are confused*

1 Answer

0 votes

Answer:

The simplified given expression
(3x^2y^(-1))/(2x).(10x^2y)/(3y^(-3)) is
5x^3y^3

Explanation:

Given expression is


(3x^2y^(-1))/(2x).(10x^2y)/(3y^(-3))

To find the simplified expression:


(3x^2y^(-1))/(2x).(10x^2y)/(3y^(-3))=(3x^2.x^-1)/(2y^1).(10x^2y.y^3)/(3) ( Using the properties
(a^m)/(a^n)=a^(m-n) and
a^m.a^n=a^(m+n) )


=(3x^(2-1))/(2y).(10x^2y^(1+3))/(3)


=(3x)/(2y).(10x^2y^4)/(3) (using division property to the terms)


=5x^(1+2)y^(4-1) ( Using the properties
(a^m)/(a^n)=a^(m-n) and
a^m.a^n=a^(m+n) )


=5x^3y^3

Therefore
(3x^2y^(-1))/(2x).(10x^2y)/(3y^(-3))=5x^3y^3

Therefore the simplified given expression is
5x^3y^3

Therefore simplified expression is given by
(3x^2y^(-1))/(2x).(10x^2y)/(3y^(-3))=5x^3y^3

User Tom Bush
by
4.8k points